THE ANALYSIS OF STUDENTS’ ATTITUDE TO THE CLASSROOM ENVIRONMENT IN SMPN 2 MAYANG - Dini Atrasina Ludyas Adani; Wachju Subchan (ScienceEdu: Jurnal Pendidikan IPA, 2020)
This study was aimed to determine students' caring behavior towards cleanliness and neatness of the messy environment, especially in their classrooms. This study used a descriptive qualitative research design. This study used a population of grade VII students at SMP Negeri 2 Mayang. The total number of class VII students in SMP Negeri 2 Mayang was 167 students. Samples taken used in this study were 124 students. The sample selection was done by a proportional random sampling method. The data collection technique used in the research was in the form of a Google form questionnaire. Based on the result, shows that 73.85% or 92 students had a good sense of environmental care because they wanted to clean the classroom when the condition was not neat, while students who were less concerned as much as 18.17% or 22 students. They still asked friends to clean the dirt in the class. For students who do not care about the environment as much as 10 students or 7.99%, because students were indifferent even though the class is dirty.